Charisma and canon: essays on the religious history of the Indian subcontinent - Dalmia, Vasudha; Malinar, Angelika; Christof, Martin (New Delhi: Oxford University Press, 2001)
Papers presented at a symposium held at Blaubeuren, Germany from May 17-21, 1997.
Includes bibliographical references.
Keywords: INDIA- RELIGION